2017
DOI: 10.1089/trgh.2017.0020
|View full text |Cite
|
Sign up to set email alerts
|

Transgender and Gender Nonconforming Youths' Public Facilities Use and Psychological Well-Being: A Mixed-Method Study

Abstract: Purpose: In this study, we explored experiences and feelings of safety in public facilities in relation to psychological well-being among transgender and gender nonconforming (TGNC) youth in the Midwest in the summer of 2016, in the context of ongoing legislative proposals and regulations regarding school and public bathroom use in the United States.Methods: We used a mixed-method approach, with (1) a self-administered, paper-and-pencil survey of 120 TGNC youth, focusing on differences of self-esteem, resilien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 21 publications
(29 reference statements)
1
24
0
Order By: Relevance
“…[34][35][36][37][38][39][40][41][42][43] Researchers are beginning to include TGD individuals in studies exploring the mental and physical health effects of minority stress and weathering. 5,34,35,44 Our data illustrate how minority stressors and weathering ensue through patient-provider interactions, offering tangible inlets to reduce health disparities. For example, consistent with NTDS 5 findings, our participants described having to repeatedly educate providers steeped in ciscentric, binary views.…”
Section: Medical Model In Contextmentioning
confidence: 84%
“…[34][35][36][37][38][39][40][41][42][43] Researchers are beginning to include TGD individuals in studies exploring the mental and physical health effects of minority stress and weathering. 5,34,35,44 Our data illustrate how minority stressors and weathering ensue through patient-provider interactions, offering tangible inlets to reduce health disparities. For example, consistent with NTDS 5 findings, our participants described having to repeatedly educate providers steeped in ciscentric, binary views.…”
Section: Medical Model In Contextmentioning
confidence: 84%
“…Furthermore, as most youth spend a substantial amount of their time in schools, the finding that victimization and perceived discrimination contribute to these disparities suggests that schools should enact anti-discrimination and anti-bullying policies inclusive of protections for LGBTQ youth [11]. Such policies should specifically address the needs and concerns of transgender and nonbinary youth, such as allowing youth to use the bathroom that corresponds with their gender identity and their chosen name, in addition to requiring that school officials respect their pronouns, all of which have been found to improve health outcomes [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The 2015 Youth Risk Behavior Survey (YRBS), (31) reported that among self-identi ed sexual minority students, 34% of them were bullied on school property and 28% were bullied electronically. In a sample of 120 TGN youth in Weinhardt et al, (32) about 46% reported that they experienced discrimination in bathrooms and 56% felt unsafe using bathrooms in public due to their appearance or gender identity. Additionally, studies have found that LGBTQ youth were three times more likely to drop out of high school compared to the general population.…”
Section: Discussionmentioning
confidence: 99%